2022
DOI: 10.1002/mdc3.13449
|View full text |Cite
|
Sign up to set email alerts
|

Prosaccade and Antisaccade Behavior in Fragile X‐Associated Tremor/Ataxia Syndrome Progression

Abstract: Background Quantitative measurement of eye movements can reveal subtle progression in neurodegenerative diseases. Objective To determine if quantitative measurements of eye movements may reveal subtle progression of fragile X‐associated tremor and ataxia (FXTAS). Methods Prosaccade (PS) and antisaccade (AS) behavior was analyzed in 25 controls, 57 non‐FXTAS carriers, and 46 carriers with FXTAS. Results Symptomatic individuals with FXTAS had longer AS latencies, increased rates of AS errors, and increased AS dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 23 publications
(48 reference statements)
5
6
0
Order By: Relevance
“…Prior studies of saccade behavior in asymptomatic premutation carriers have documented mixed findings suggesting both impaired and spared latencies and preserved accuracy ( Shelton et al, 2014 ; Wong et al, 2014 ; Moser et al, 2021 ). Recently, McLennan et al extended these findings by including FXTAS+ premutation carriers in a primarily male sample and showed that saccade accuracy was more variable in FXTAS patients compared to asymptomatic premutation carriers, though this effect did not survive corrections for multiple comparisons ( McLennan et al, 2022 ). Here, we focus on a predominantly female sample and show that saccade latency and accuracy each appear to be unaffected during initial disease stages.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior studies of saccade behavior in asymptomatic premutation carriers have documented mixed findings suggesting both impaired and spared latencies and preserved accuracy ( Shelton et al, 2014 ; Wong et al, 2014 ; Moser et al, 2021 ). Recently, McLennan et al extended these findings by including FXTAS+ premutation carriers in a primarily male sample and showed that saccade accuracy was more variable in FXTAS patients compared to asymptomatic premutation carriers, though this effect did not survive corrections for multiple comparisons ( McLennan et al, 2022 ). Here, we focus on a predominantly female sample and show that saccade latency and accuracy each appear to be unaffected during initial disease stages.…”
Section: Discussionmentioning
confidence: 99%
“…Antisaccade latency and the proportion of trials in which participants looked toward rather than away from the peripheral target (antisaccade error) were examined. Inhibitory cost was calculated as the difference between VGS latency and antisaccade latency with greater values representing greater inhibitory cost, or lower efficiency in inhibiting unwanted saccades ( Wong et al, 2014 ; McLennan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations